2021
DOI: 10.1111/1541-4337.12740
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric barrier discharge cold atmospheric plasma: Influence of processing parameters on microbial inactivation in meat and meat products

Abstract: Decontamination of meat is commonly practiced to get rid of or decrease the microbial presence on the meat surface. Dielectric barrier discharge cold atmospheric plasma (DBD‐CAP) as innovative technology is a food microbial inactivation technique considered in high regard by food scientists and engineers in present times. However, cold atmospheric plasma application is at the experimental stage, due to lack of sufficient information on its mode of action in inactivating microbes, food shelf‐life extensibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 158 publications
(325 reference statements)
0
20
0
Order By: Relevance
“…A large number of RONS is generated during the HVACP treatment process; they can damage the cell wall and membrane to cause the leakage of cytoplasm [ 25 ], and parts of the RONS can move through the cell membrane to damage the nucleic acid, DNA, protein, and other important compositions inside the cell causing the death of cells [ 26 ]. Olatunde et al [ 27 ] investigated the effects of DBD cold plasma treatment on the quality of Asian Sea Bass Slices packaged with 10% oxygen and 90% argon during storage, and they found that the microbial count in the treatment groups was still in the acceptable range after 12 d, while that of the control group was higher than the acceptable range after 6 d.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of RONS is generated during the HVACP treatment process; they can damage the cell wall and membrane to cause the leakage of cytoplasm [ 25 ], and parts of the RONS can move through the cell membrane to damage the nucleic acid, DNA, protein, and other important compositions inside the cell causing the death of cells [ 26 ]. Olatunde et al [ 27 ] investigated the effects of DBD cold plasma treatment on the quality of Asian Sea Bass Slices packaged with 10% oxygen and 90% argon during storage, and they found that the microbial count in the treatment groups was still in the acceptable range after 12 d, while that of the control group was higher than the acceptable range after 6 d.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, HVCP processing has been extensively used as a NTT for the enzymes inactivation in FJs [7] , [87] , [98] , [99] , [100] , [101] , [102] . It is based on protons, electrons, atoms, and ions in their excited and ground states.…”
Section: High Voltage Electric Field Cold Plasma (Hvcp)mentioning
confidence: 99%
“…Legend; 1, Indicator; 2, Exhaust fan; 3, Touch screen control panel; 4, Frequency converter; 5, Power distribution box; 6, Electric voltage regulator; 7, Inductance 1; 8, Inductance 2; 9, Wheels; 10, Power cable inlet; 11, High voltage transformer; 12, lower electrode; 13, upper electrode; 14, lifting mechanism; 15, Frame; 16, Sample position. Adapted from Nasiru, Frimpong [99] with permission.
Fig.
…”
Section: High Voltage Electric Field Cold Plasma (Hvcp)mentioning
confidence: 99%
“…The relationship between VOCs and reactive species is not definite because of the variations in the reactive species’ life span. Thus, the amount and number of VOCs’ generation depend on the life span of the reactive species created by the HVCP [ 15 , 55 ]. Another factor for the variation might be the various intermolecular forces, including non-covalent bonds, van der Waals forces, and hydrogen bonding formed when EWP interact with HVCP [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nonthermal processing technique is a food processing technique that is achieved at room temperatures; it preserves food materials’ attributes whilst minimally affecting those attributes, thus preventing flavour loss, maintaining nutritional components, and extending the shelf life of the food materials [ 15 , 16 ]. High-voltage cold plasma (HVCP) is among the novel nonthermal processing techniques gaining attention lately from the scientific community.…”
Section: Introductionmentioning
confidence: 99%